(3GdYOGdI GdGLJeGYjI cGge QcGFR GdHfjGf GdeGdi ai GdTQjYI GdGSdGejI hai GdGfXeI GdhVYjI GdeYGUQI eY GdGTGQI Gdi eUQ (B/ s - (3NejS eMeO gQhf GHhHcQs; (3YHOGdMajX YHOGddg YjO s; (3eMehO HdGd egQGf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3JOhQ gPg GdQSGdI Mhd GdYOGdI GdGLJeGYjI GdYOGdI GdGLJeGYjI HGYJHGQgG Gge QcGFR GdHfjGf GdeGdi ai GdTQjYI GdGSdGejI hai GdGfXeI GdhVYjI GdeYGUQI eY GdGTGQI Gdi eUQ ai GdfXe GdeGdjI GdebGQfI HGYJHGQ Gf eTcdI GdYOGdI GdGLJeGYjI eTcdI YGeI hgGeI hNWjQI (B: (3hPGJ GKGQ cHjQI Ydi GdJfejI ai GdeLGdGJ GdGbJUGOjI hGdGLJeGYjI hZjQgG ef GdeLGdGJ(B.(3aHJf dfG Gf GdfXe GdhVYjI bO bGeJ abW Ydi Gdbje GdeGOjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdTQjYI GdGSdGejI, (B2007s
(3HHdjhLQGajG(B: (3UaMGJ (B397-412s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdTQjYI GdESdGejIs; (3GdGfXeI GdeYGUQIs; (3GdHfjGf GdeGdi ai GdTQjYI GdGSdGejIs; (3GdYOGdI GdGLJeGYjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdTQjYI GdESdGejIs